Effect of potassium sorbate, nisin and lysozyme singly and in combinations on the quality of pickled white cheese during storage - Alan, Selcuk; Oksuztepe, Gulsum; Guran, Husnu Sahan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
This study was conducted to determine the effects of potassium sorbate, nisin, and lysozyme on the microbiological, chemical, and sensory quality of pickled white cheeses during their shelf life. For this purpose, & Scedil;avak white cheese, experimentally produced with a mixture of 50% sheep's milk and 50% cow's milk, was sliced (4x4x4 cm) and stored in a 16% brine solution containing potassium sorbate (1 gml(-1)), nisin (12.5 mgl(-1)), and lysozyme (200 mgl(-1)), alone or in combination, at 4 degrees C for 90 days. At the end of storage, statistically significant differences were found between the combination group using potassium sorbate 1 gL--(1) + nisin 12.5 mgL--(1) and the control group in terms of antimicrobial effect levels against coliforms, Enterobacteriaceae, fecal streptococci, lipolytic and proteolytic bacteria, and E. coli ( P <= 0.05). No statistically significant differences were found between the groups in terms of sensory evaluation ( P > 0.05). However, according to the numerical scores given, group 4 (potassium sorbate 1 gL--(1) + nisin 12.5 mgL--(1)) and group 7 (potassium sorbate 1 gL--(1) + nisin 12.5 mgL--(1) + lysozyme 200 mgL--(1)) were the two most highly rated groups in terms of sensory evaluation, with equal scores (95.55). It was concluded that the combination of potassium sorbate 1 gL-1 + nisin 12.5 mgL-1, which is an additive with the status of General Recognized as Safe and complies with legislation for its use in brined cheeses offered for sale, can be safely used as an alternative method to heat treatment to improve the quality of pickled white cheeses and that it contains data that can form the basis for further studies to investigate how these additives may also have effects on some pathogenic bacteria.
Efecto del sorbato de potasio, la nisina y la lisozima, individualmente y en combinación, sobre la calidad del queso blanco encurtido durante el almacenamiento
Keywords: Potassium sorbate; nisin; lysozyme; white cheese; shelf life